A Space-Vector Analysis of the Twelve-Pulse Diode Bridge Rectifier Operation for the Auxiliary Circuit Current Determination Providing the Optimal Line Currents’ THD - Jaroslaw Rolek; Grzegorz Utrata (Energies)
Three-phase diode bridge rectifiers are widely employed in various industrial applications because of their inherent simplicity, robustness, low electromagnetic interference and good overall performance. However, their use causes harmonic distortion in the electric power network line currents due to their nonlinear nature, which, in turn, affects the electric power quality. The fundamental approach to limit the line currents’ total harmonic distortion (THD) introduced by the diode bridge rectification systems is based on increasing the number of steps in their waveform per power supply cycle and drawing them closer to the pure-sine waveforms. This can be achieved by employing the conventional twelve-pulse rectification system composed of two parallel connected six-pulse diode bridge rectifiers, in which the DC circuit is expanded on the auxiliary circuit responsible for adequately shaping the line currents’ waveforms per power supply cycle. When the auxiliary circuit is connected to the interphase reactor (IPR) additional (secondary) winding, the ability of the rectification system to reduce the line current THD depends mainly on the auxiliary circuit current waveform and its parameters. This paper provides a space vector analysis of the twelve-pulse diode bridge rectifier operation. It leads to devising a formula for the auxiliary circuit current related to the phase angle of the rectification system line currents’ space vector and the load current, which has been missing in the literature so far. The formula explicitly defines the auxiliary circuit current waveform that guarantees the optimal line currents’ THD for the twelve-pulse diode bridge rectifier which is expanded with the auxiliary circuit connected to the IPR secondary winding. The theoretical studies are validated through experimental investigations.